UNDERSTANDING LEARNER- CHARACTERISTICS: PSYCHOLOGICAL FACTORS AND LANGUAGE DEVELOPMENT - Umurkulova Gulnoza Ismoilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Language learning is a complex and multifactorial process, in which not only intellectual, but also psychological factors play an important role. Each student has his own  individual  psychological  portrait,  and  this  aspect  determines  their  success  in language acquisition. Therefore, the teacher must deeply analyze the psychological characteristics of students and be able to approach them individually. Motivation is an internal or external force that encourages a student to learn a language. Integrative (interest in culture and society) and instrumental (professional or educational goals) motivations directly affect students' language acquisition. Students  with  a  high  level  of  anxiety  have  more  difficulty  learning  a  new language.  They  are  afraid  of  making  mistakes  and  do  not  engage  in  active communication, which slows down language development.